Adipose-derived Stem Cells as a Potential Additive Therapy in Chronic Compression Neuropathy in Rodents: a Diffusion Tensor Imaging Study. Issue 1 (April 2016) - Sottaz, Lima; Schären, Stefan; Madduri, Srinivas; Schäfer, Dirk; Kalbermatten, Daniel
Introduction: Compression neuropathy and nerve root compression are a leading cause of morbidity as well as a major cause of work impairment. Surgical and conservative treatments are widely used but there is still a lack of long-lasting effects. We seek to provide an additive therapy consisting of injected adipose-derived stem cells (ASCs) in the epineurium of a chronic nerve compression rodent model. In animal studies, evaluation of peripheral nerve injury and therapy monitoring is commonly performed using clinical scoring and histopathological workup. Recent developments in magnetic resonance imaging allow for the direct evaluation of nerve fiber integrity. Here we present the evaluation of this imaging method, diffusion tensor imaging (DTI) in the context of chronic sciatic nerve compression. Material and Methods: We created a compressive lesion with a polymer clip on the left sciatic nerve of Sprague-Dawley rats. 0.5 million ASCs were injected in the epineurium under ultrasound guidance two weeks after the crush injury in a first group. The second group was injected with culture medium as control. The clips were removed in a third group who benefited from an intraoperative injection of ASCs and a fourth group underwent the same procedure but received the sham injection. Gait analyses with calculation of the Sciatic-Function-Index using a computed track were performed before the cells or sham injections as well as after two and four weeks. Two weeks post injection, respectively four weeks, post-mortem imaging was acquired on a 3-Tesla scanner. The Fractional Anisotropy (FA), a measure of fiber integrity, was measured for the proximal and distal part of the lesion and for the contralateral nerve. Afterwards, histomorphometry of cross sections of the nerve, histochemistry for muscle fiber typing and calculation of the gastrocnemius muscle weight ratio were undertaken. Results: The FA showed no differences between the injured and uninjured side at the proximal site. Distally, the FA was clearly reduced on the injured side. The FA in the group treated with ASCs who underwent clip removal was significantly higher as well as the FA ratio (distal value/ proximal value). These findings could be correlated with clinical and histological analyses that showed faster regeneration and faster clinical recuperation in this group associated with reduced muscle atrophy. Conclusion: ASCs alone seem to be insufficient to provide a clinically relevant treatment in this context of severe crush injury. Nonetheless, regenerative cells could be an interesting additive therapy after surgical decompression. Furthermore, our results indicate that DTI may be used to quantitatively assess sciatic nerve injury after treatment using ASCs in a rat model.